Botryodeorsum – a new genus of Moniliales from India - and O.P. SINGH, T. PRAMEELA DEVI*, NITA MATHUR, P.N. CHOWDHRY, JASVIR SINGH (Indian Phytopathology, 2006)
A new hyphomycetous fungus of Moniliales group, Botryodeorsum indicum gen. et, sp. nov. is illustrated and described from India.The genus is characterized by branched, long, erect, hyaline conidiophore bearing around stout lateral stalks down ward; forming 3-5 oval to round vesicles directly on the stalk; producting many aseptate, hyaline, oval to ellipsoidal, rough, apiculate conidia on denticles; and soft, round to irregular dark brown sclerotia.